Effect of puberty on the immune system: Relevance to multiple sclerosis - Ucciferri, Carmen C.; Dunn, Shannon E. (Frontiers in Pediatrics, 2022)
Puberty is a dynamic period marked by changing levels of sex hormones, the development of secondary sexual characteristics and reproductive maturity. This period has profound effects on various organ systems, including the immune system. The critical changes that occur in the immune system during pubertal onset have been shown to have implications for autoimmune conditions, including Multiple Sclerosis (MS). MS is rare prior to puberty, but can manifest in children after puberty. This disease also has a clear female preponderance that only arises following pubertal onset, highlighting a potential role for sex hormones in autoimmunity. Early onset of puberty has also been shown to be a risk factor for MS. The purpose of this review is to overview the evidence that puberty regulates MS susceptibility and disease activity. Given that there is a paucity of studies that directly evaluate the effects of puberty on the immune system, we also discuss how the immune system is different in children and mice of pre- versus post-pubertal ages and describe how gonadal hormones may regulate these immune mechanisms. We found evidence that puberty enhances the expression of co-stimulatory molecules and cytokine production by type 2 dendritic cells (DC2s) and plasmacytoid dendritic cells (pDCs) and increases T helper 1 (Th1), Th17, and T follicular helper immunity as well as promotes immunoglobulin (Ig)G antibody production. Overall, this review highlights how the immune system undergoes a functional maturation during puberty, which has the potential to explain the higher prevalence of MS and other autoimmune diseases in adolescence, especially in females.